Policy Implementation Analysis of the Village Fund Cash Assistance Program in Reducing the Expenditure Burden of the Poor in Gegerbitung Sub-district, Sukabumi District - Tantan, Tantan; Saleh, Munandi; Nur, Tuah (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the implementation of the Village Fund Direct Cash Assistance (BLT-DD) policy in reducing the expenditure burden of poor households in Gegerbitung District, Sukabumi Regency. Using a descriptive qualitative approach, the study evaluates the effectiveness of the policy through five key indicators: policy standards and targets, resources, inter-organizational communication, characteristics of implementers, and social, economic, and political conditions. Findings show that while BLT-DD generally benefits the community, several issues hinder its effectiveness, including mistargeting, limited public understanding, and funding constraints. Out of 325 beneficiary households, 159 were inaccurately targeted. Public dependence on aid has also become a significant challenge. Furthermore, socio-political factors such as data manipulation for local political interests worsen aid distribution. The study concludes that successful policy implementation heavily relies on synergy among implementing agents and supportive environmental conditions. Continuous evaluation, accurate data collection, and intensive public outreach are crucial for the program’s success.